Biologics in Paediatric Crohn's Disease - Oliver Gouldthorpe; Anthony G. Catto-Smith; George Alex (Gastroenterology Research and Practice)
Crohn's disease affects increasing numbers of children worldwide. Generally, childhood-onset disease runs a more severe course than in adults and has a greater impact on quality of life. Therapy in children must take account of a different set of risks for toxicity compared to adults, but also to their longevity. Biologic drugs present remarkable advantages in terms of disease control for children, especially in those whose disease cannot be controlled with conventional therapies, but their long-term risks are still being assessed. Data regarding biologic use in children is limited and mostly amounts to case series, but results have been promising, both in terms of controlling disease activity and improving growth parameters. Adverse reactions are infrequent in the short term, but loss of response is a long-term problem, particularly in children. More information is needed about very long term risks. Infliximab and adalimumab are the most studied agents in children, while there is relatively limited data on certolizumab and natalizumab. Further collection of data on these agents is still needed, but this should not restrict access to these agents for children in whom no other agent is effective.